The AI-Powered Sentinel: Wearable Technology's Role in Proactive Elderly Care and Fall Prevention - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The global demographic shift towards an aging population presents significant challenges to healthcare systems, with falls in the elderly standing out as a m...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Machine Learning; Wearable Technology